The worm whisperer - Hicks, Betty; Hatke, Ben (New York : Roaring Brook Press, 2013)
Ellison Ellis Coffey, a lonely fifth-grader, discovers he might have the special gift of talking to bugs and decides to use his ability to win his town's annual Woolly Worm Race.
Publisher's Weekly, November 2012
Booklist, December 2012
Kirkus Review, November 2012
4.3
3-6
Keywords: Worms -- Juvenile fiction; Insects -- Juvenile fiction; Human-animal communication -- Juvenile fiction; Racing -- Juvenile fiction; Worms -- Fiction; Insects -- Fiction; Human-animal communication -- Fiction; Racing -- Fiction; Worms -- Fiction; Insects -- Fiction; Human-animal communication -- Fiction; Racing -- Fiction